Corporate governance mechanisms and performance of banks in Africa: Empirical evidence from Nigeria - Muktar, Itai M.; Bashari, Nafisa; Ailemen, Ikpefan O.; Timilehin, Olubiyi, O. (Edelweiss Applied Science and Technology, 2025)
The varied results in assessing corporate governance in banks may be attributable to the utilization of various measures considering endogeneity issues in different contexts. This study offers new insights to address the inconsistencies in the corporate governance literature concerning the effects of corporate governance mechanisms. Therefore, this study investigates how corporate governance affects the performance of selected Nigerian deposit money banks, one of Africa’s largest economies. The research purposively selected ten (10) deposit money institutions. From 2013 to 2023, a ten-year span of business activities provided the secondary data used in the study. Subsequently, a post-estimation test and a panel estimation approach incorporating random effects, fixed effects, and pooled OLS were employed to analyze the data produced for the research. Both the fixed effect and random effect Hausman tests were run. The fixed effect model was thus chosen in light of the special circumstances that required the selection of either effect as per the Hausman test. The findings demonstrated that, throughout the study period, the performance of the deposit money institutions in Nigeria was positively impacted by board size (BOS), board composition (BOC), and directors' equity interest (DEI), in both substantial and minor ways. The study thus suggests that to fully realize the potential advantages of having a diverse board membership, attention should be directed towards alternative governance or support arrangements. Likewise, while board independence, competency, and diversity are more closely associated with bank performance, laws should emphasize these attributes rather than dictating DMOs' preferred board sizes.